MENDEFINISIKAN KEMBALI “MONEY POLITICS” SEBAGAI TRANSAKSI PEMILU DALAM PENGAWASAN PEMILU DI INDONESIA - Endri Sanopaka (Jurnal Bawaslu Provinsi Kepulauan Riau, 2019)
The practice of "Money Politics" becomes more prominent in every electoral election, be it legislative elections or regional headelections. The role of the Election Supervisory Body as dwarfed is only to supervise something abstract called "Money Politics". The concept of "Money Politics" which translates to Money Politics needs to be redefined conceptually, because Money Politics becomes a narrow noun translated limited to giving money or other forms in order to influence voters who form a Patron-Clients relationship. This article wants to offer a conceptual understanding of "Money Politics" to "Political Money" in the practice of election transactions so that reports of election violations to the Election Supervisory Board are not abstract and weaken the evidence that is already owned. The 2019 General Election and Presidential Election case illustrates the practiceof electoral transactions using political money.